Doing Duo – a Case Study of Entrainment in William Forsythe’s Choreography “Duo” - Waterhouse, Elizabeth; Watts, Riley; Bläsing, Bettina E. (Frontiers in Human Neuroscience, 2014)
Entrainment theory focuses on processes in which interacting (i.e. coupled) rhythmic systems stabilize, producing synchronization in the ideal sense, and forms of phase related rhythmic coordination in complex cases. In human action, entrainment involves spatiotemporal and social aspects, characterizing the meaningful activities of music, dance, and communication. How can the phenomenon of human entrainment be meaningfully studied in complex situations such as dance? We present an in-progress case study of entrainment in William Forsythe's choreography Duo, a duet in which coordinated rhythmic activity is achieved without an external musical beat and without touch-based interaction. Using concepts of entrainment from different disciplines as well as insight from Duo performer Riley Watts, we question definitions of entrainment in the context of dance. The functions of chorusing, turn-taking, complementary action, cues and alignments are discussed and linked to supporting annotated video material. While Duo challenges the definition of entrainment in dance as coordinated response to an external musical or rhythmic signal, it supports the definition of entrainment as coordinated interplay of motion and sound production by active agents (i.e., dancers) in the field. Agreeing that human entrainment should be studied on multiple levels, we suggest that entrainment between the dancers in Duo is elastic in time and a propose how to test this hypothesis empirically. We do not claim that our proposed model of elasticity is applicable to all forms of human entrainment nor to all to examples of entrainment in dance. Rather, we suggest studying higher order phase correction (the stabilizing tendency of entrainment) as a potential aspect to be incorporated into other models.